The Ethical Side of Economic Learning Integration: Empirical Study of Prospective Economic Teacher - Lina Rifda Naufalin; Cicilia Dyah Sulistyaningrum Indrawati; Mintasih Indriayu; Leny Noviani (FKIP Universitas Lampung, 2024)
The Ethical Side of Economic Learning Integration: Empirical Study of Prospective Economic Teacher. Objective: Technological Pedagogical Content Knowledge as a knowledge framework regarding the integration of technology and pedagogy in developing learning content in accordance with the demands of the 21st century is currently starting to touch on ethical aspects in its implementation. This research aims to describe TPACK and knowledge about digital ethics among prospective economics teacher students as a provision for implementing ethical TPACK after entering the world of work.. Method: Descriptive quantitative methodology was used using a Likert scale questionnaire. The dimensions studied include self-perception of professional ethical knowledge, technological ethical knowledge, pedagogical technological ethical knowledge, and economics disciplinary technological ethical knowledge. Prospective economics teacher students are the population in this study. The sample of 155 was determined using convenience sampling. Findings: The results of the research show that the dimensions of knowledge about professional ethics, knowledge of technology ethics, knowledge of pedagogical technology ethics, knowledge of scientific discipline technology ethics are in the very good and good categories. However, the ethical aspect of technology still needs to be improved. Conclusion: This research contributes to the preparation of the learning curriculum for prospective economics teacher students so that prospective economics teachers have the skills to apply TPACK by paying attention to ethics therein. Keywords: digital ethics, TPACK, prospective teacher students.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202489